2012
DOI: 10.3168/jds.2011-4683
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different footbathing frequencies using copper sulfate in the control of digital dermatitis in dairy cows

Abstract: Two experiments were conducted to test the effectiveness of different footbathing frequencies using CuSO₄ in the control of digital dermatitis (DD) in groups of dairy cows with low and high DD prevalence in an endemically infected herd. During the study, groups of cows walked through allocated footbath solutions after milking on 4 consecutive milkings each week, 2 wk, or monthly, depending on treatment. The footbath solutions were changed either after 200 cows had passed through the footbath or within 24 h. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Proper footbath design has been evaluated and is based on dimensions (Cook, Rieman, Gomez, & Burgi, 2012;Logue, Gibert, Parkin, Thomson, & Taylor, 2012), frequency of use, product used and appropriate concentration of solution (Relun et al, 2012;Speijers et al, 2010Speijers et al, , 2012Teixeira, Machado, Caixeta, Pereira, & Bicalho, 2010). When used, the footbath must be managed to ensure sufficient solution is consistently available to achieve full immersions of hooves of all four feet .…”
Section: Footbathsmentioning
confidence: 99%
“…Proper footbath design has been evaluated and is based on dimensions (Cook, Rieman, Gomez, & Burgi, 2012;Logue, Gibert, Parkin, Thomson, & Taylor, 2012), frequency of use, product used and appropriate concentration of solution (Relun et al, 2012;Speijers et al, 2010Speijers et al, , 2012Teixeira, Machado, Caixeta, Pereira, & Bicalho, 2010). When used, the footbath must be managed to ensure sufficient solution is consistently available to achieve full immersions of hooves of all four feet .…”
Section: Footbathsmentioning
confidence: 99%
“…findings of this study some other intervention studies found an increase of DD prevalence after a longer period of successful footbath usage (1,3,18,19,22). Possibly the duration of our study was too short to show this effect and a repetition of the study with a longer period of footbathing would be reasonable.…”
Section: Conclusion For Practicementioning
confidence: 44%
“…However, this effect was only seen in 1 of 3 possible combinations of DD lesion scorings. Speijers et al (2012) evaluated the effect of different hoof-bathing frequencies and found that more frequent use of copper sulfate hoof baths resulted in more cows without DD lesions. Also in this study severe cases of DD were treated topically with antibiotics.…”
Section: Short Communicationmentioning
confidence: 99%
“…Only the study of Speijers et al (2010) had an evaluation of the efficacy of copper sulfate (and hypochlorite) as the primary objective. In a follow-up study the same group later evaluated the effect of different treatment frequencies (Speijers et al, 2012).…”
Section: Short Communicationmentioning
confidence: 99%